2019
DOI: 10.1002/micr.30469
|View full text |Cite
|
Sign up to set email alerts
|

Vascular pedicle division during free flap re‐inset in pharyngoesophageal reconstruction

Abstract: Background Free intestinal flaps for pharyngolaryngoesophagus reconstruction may require revision operations, including free flap re‐inset for functional improvement. This report aimed to present our experience on vascular pedicle division at the secondary procedure of free flap re‐inset for functional improvement in pharyngoesophageal reconstruction. Patients and Methods Eight male and seven female patients, with a mean age of 52 years old (range: 28–78 years), underwent pharyngoesophageal stricture (n = 7) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…6 ). 6 12 13 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 The male-to-female ratio was 8:1. Overall, the mean age was 54.65 years (range: 20–80 years) while the average follow-up was 24.72 months (range: 1–72 months).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 ). 6 12 13 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 The male-to-female ratio was 8:1. Overall, the mean age was 54.65 years (range: 20–80 years) while the average follow-up was 24.72 months (range: 1–72 months).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported the use of postoperative chemotherapy or radiotherapy ( Table 3 ). 12 13 15 17 18 19 20 24 25 26 27 28 29 33 35 36 37 38 39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate split is obligated in reconstructions of separate defects and those requiring drastic directional changes, yet otherwise a delayed split is feasible weeks after the initial flap inset of folding or bridging across defects. 40,41 All in all, the ideal flap design should be collectively determined by multiple factors of reconstruction needs if to achieve precise and satisfactory outcomes.…”
Section: Discussionmentioning
confidence: 99%